Igreja e sociedade na Gaudium et Spes e sua incidência no Brasil - Miranda, Mário de França (Revista Eclesiástica Brasileira, 2006)
O Autor aborda o tema – Igreja e sociedade na Gaudium et Spes e sua incidência no Brasil – em três passos sucessivos. Primeiramente, recupera, na memória e de modo breve e conciso, as linhas fundamentais da relação Igreja e sociedade no período imediatamente pré-conciliar; em seguida, com este pano de fundo, examina esta mesma relação na Gaudium et Spes, para, finalmente e de modo especial, examiná-la com relação à sociedade brasileira atual e propor uma maior participação dos leigos católicos. Abstract: The author deals with the subject – Church and Society in the Gaudium et Spes and their incidence in Brazil – in three successive steps. First he retraces, in the historical records and in a brief and concise style, the fundamental lines of the relationship Church and society in the period immediately before the Council; next and with this as background, he examines the same relationship in the Gaudium et Spes; and finally, in a very specific way, he examines the relationship as it occurs in current Brazilian society and proposes a greater participation of the Catholic laity.